Out of order : storytelling techniques for video and cinema editors - Hockrow, Ross (San Francisco : Peachpit Press, 2015)
"Learn workflow tips, time saving techniques, linear and non-linear theory, cutting techniques, enhancing emotion through music and sound effects, leveling and mastering audio, color correction, and most importantly, the role editing can have on the telling of the story. Additional techniques are shown through multiple step-by-step videos available on the author's site as well as clips from a documentary the author created on editing."--Publisher's website.
The story arc -- Conflict and shot selection -- Ordering clips and scenes -- Pacing: timing and types of cuts -- Rhythm and time -- Editing audio -- The editing process -- Appendix: Film and TV show references.
Includes filmography (pages 204-212) and index.
Keywords: Motion pictures -- Editing; Motion picture authorship